Postural control of prolonged standing in people with Parkinson's disease - Coelho, Daniel Boari (2024)
People with Parkinson's disease (pwPD) have reduced adaptability to postural control during prolonged standing compared to neurologically healthy individuals (control). Objective. The study aimed to characterize postural changes during prolonged standing and their effect on postural control in pwPD compared to control. We recorded the body sway of the second lumbar vertebra of 23 pwPD and 23 control while they performed prolonged standing (15 min). The number and amplitude of the body sway patterns (shifts, fidgets, and drifts), the root mean square, velocity, and frequency of the body sway were analyzed. The number of shifts in the anterior-posterior (AP) and medial-lateral (ML) directions was greater for the pwPD than the control. In addition, the amplitudes of shifts in the AP direction and fidgets in the AP and ML directions were greater for the pwPD than the control. Our results show that: (1) A larger number of shifts of body sway suggest references positions are frequently changing; (2) Fidgets is a pumping mechanism and can be sensory-demand action to restore mechanoreceptors activity on the foot sole; and (3) No drift changes may suggest there is no slow migration of reference position. We conclude that pwPD exhibits different behavior than healthy ones during prolonged standing, suggesting that prolonged standing could distinguish individuals with Parkinson's disease.